Copper-clad plate glue solution, preparation method thereof, copper-clad plate and preparation method thereof

By using polysalene resin and other resin combinations, and combining appropriate curing agents, catalysts, fillers and solvents, copper clad plate glue solution is prepared, which solves the problem that traditional copper clad plate cannot meet the demand for dielectric constant and dielectric loss of high-frequency and high-speed electronic information products, and realizes copper clad plate with small dielectric constant, low loss, high thermosetting and good flame retardant performance.

CN119505467APending Publication Date: 2025-02-25SHANDONG JINBAO ELECTRONICS
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411428469.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Traditional copper clad plates cannot meet the demand for high-frequency and high-speed electronic information products for small dielectric constant and low dielectric loss.

Method used

A copper clad rubber liquid is prepared by using polyacene resin as the main resin, combined with benzoxazine resin, PPO resin and biphenyl epoxy resin, combined with curing agent, catalyst, filler and solvent. The glue solution reduces the dielectric constant and dielectric loss of the copper clad plate through a specific assembly distribution ratio and preparation process.

Benefits of technology

The dielectric constant of the copper clad plate is less than 3.0, the dielectric loss is less than 0.003, the thermosetting is high, the flame retardant reaches FV-0 level and the peel strength is higher than 0.9N/mm, meeting the needs of high-frequency and high-speed copper clad plates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005082876160000081
    Figure BDA0005082876160000081
Patent Text Reader

Abstract

The invention relates to the technical field of copper-clad plates, in particular to a copper-clad plate glue solution and a preparation method thereof, and a copper-clad plate and a preparation method thereof. The copper-clad plate glue solution provided by the invention comprises resin, a curing agent, a catalyst, a filler and a solvent, the resin comprises polyacenaphthene resin. The copper-clad plate prepared from the copper-clad plate glue solution has the dielectric constant of lt; 3.0, a dielectric loss (10G) lt; 0.003, Tgt, 0.003, Tgt; the temperature is 210 DEG C, and T288gt; after 120 minutes, the flame retardance reaches FV-0 level, and the peel strength is gt; the copper-clad plate has low dielectric constant, low loss and compatibility with high frequency, other indexes are not reduced, the comprehensive performance is excellent, and the requirements of the high-frequency and high-speed copper-clad plate are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper clad laminates, and in particular to a copper clad laminate adhesive and a preparation method thereof, a copper clad laminate and a preparation method thereof. Background Art

[0002] With the advancement of science and technology, the development of high-frequency communication has led to the development of wireless communication towards high frequency, and the frequency of use has shifted from the MHz band to the GHz band, and information transmission has entered the high-frequency field. The high-frequency and high-speed electronic information products have also placed higher requirements on the high-frequency characteristics of copper clad laminates. The dielectric constant (Dk) is required to be small and very stable, and the smaller the better, because the signal transmission rate is inversely proportional to the square root of the material's dielectric constant, and a high dielectric constant can easily cause signal transmission delays; the dielectric loss (Df) must be small, because the dielectric loss mainly affects the quality of signal transmission, and the smaller the dielectric loss, the smaller the signal loss. However, traditional copper clad laminates can no longer meet the current market demand, and the research and development of high-frequency and high-speed copper clad laminates is imperative. Summary of the invention

[0003] In order to solve the above technical problems existing in the prior art, the present invention provides a copper clad laminate adhesive and a preparation method thereof, a copper clad laminate and a preparation method thereof.

[0004] The technical solution of the present invention to solve the above technical problems is as follows:

[0005] The first aspect of the present invention is to provide a copper clad laminate adhesive, comprising a resin, a curing agent, a catalyst, a filler and a solvent; the resin comprises a polyacenaphthylene resin.

[0006] The copper clad laminate adhesive component provided by the present invention uses polyacenaphthylene resin as the main resin and is matched with other components, so that the dielectric constant (Dk) and dielectric loss (Df) of the prepared copper clad laminate are small, meeting the requirements of high-frequency and high-speed copper clad laminates.

[0007] On the basis of the above technical solution, the present invention can also make the following technical improvements:

[0008] Furthermore, the resin also includes benzoxazine resin, PPO resin, and biphenyl epoxy resin.

[0009] The beneficial effect of adopting the above further technical solution is that by adding benzoxazine resin, PPO (polyphenylene ether) resin and biphenyl epoxy resin, the resin ratio is increased, the thermosetting property is increased and the dielectric loss is reduced.

[0010] The copper clad laminate adhesive comprises the following components in parts by weight: 53 to 71 parts of polyacenaphthylene resin, 10 to 22 parts of benzoxazine resin, 22 to 26 parts of PPO resin, 14 to 28 parts of biphenyl epoxy resin, 0.3 to 0.6 parts of curing agent, 0.21 to 0.46 parts of catalyst, 59 to 77 parts of filler, and 58 to 93 parts of solvent.

[0011] The beneficial effect of adopting the above further technical solution is that the dielectric constant (Dk) and dielectric loss (Df) of the copper clad laminate can be further reduced by adjusting the ratio of each component.

[0012] Furthermore, the curing agent is DDS (4,4-diaminophenylsulfone), the catalyst is dimethyltetraethylimidazole, the filler is aluminum hydroxide and / or silicon powder, and the solvent is xylene and / or toluene.

[0013] The second aspect of the present invention is to provide a method for preparing the above-mentioned copper clad laminate adhesive, comprising the following steps:

[0014] S1: At room temperature, add resin, curing agent and part of solvent into a container and stir to dissolve to obtain a solution;

[0015] S2: At room temperature, add the catalyst into the solution of S1 and stir to dissolve to obtain a mixed solution;

[0016] S3: Add the filler into the mixed solution of S2 and stir evenly to obtain an emulsion;

[0017] S4: adding the remaining part of the solvent into the emulsion of S3, stirring and gelling, and obtaining the copper clad laminate glue.

[0018] By adopting the above steps, a uniform and stable copper clad laminate adhesive solution is obtained.

[0019] Furthermore, in S4, the gelling time is 250 to 270 s.

[0020] Furthermore, in S1, part of the solvent includes 20 to 40 parts of toluene and 18 to 27 parts of xylene, by weight; and in S4, the remaining solvent includes 10 to 13 parts of xylene and 10 to 13 parts of toluene, by weight.

[0021] The solvent is added in two parts. The part of the solvent added in S1 is used to dissolve the resin components and the curing agent, and the remaining part of the solvent added in S4 is used to adjust the viscosity of the copper clad laminate adhesive.

[0022] The third aspect of the present invention is to provide a copper clad laminate prepared by using the above copper clad laminate glue.

[0023] Another aspect of the present invention is to provide a method for preparing the copper clad laminate, comprising the following steps:

[0024] (1) The copper clad laminate adhesive is completely and evenly impregnated with the glass fiber cloth, and then baked in an oven at 150-200°C for 2-4 minutes to obtain a prepreg;

[0025] (2) Take several prepregs with smooth surfaces and uniform coating, stack them, attach copper foil on the top and bottom, place them in a vacuum hot press with a pressure of 5-17 MPa and a temperature of 160-210°C, hot press for 2-4 hours and keep warm for 0.5-2 hours to obtain a copper clad laminate.

[0026] Furthermore, the prepreg has a glue content of 49-57 wt %.

[0027] Furthermore, the glass fiber cloth is Low DK (low dielectric constant) glass fiber cloth.

[0028] Compared with the prior art, the present invention has the following technical effects:

[0029] (1) The present invention uses polyacenaphthylene resin, benzoxazine resin, PPO resin, biphenyl epoxy resin, curing agent DDS, catalyst combined with solvent and filler to provide another possibility for the preparation of high-frequency and high-speed copper clad laminates;

[0030] (2) The present invention uses polyacenaphthylene resin as the main resin, and adds benzoxazine resin, PPO resin, and biphenyl epoxy resin to increase the resin ratio. The benzoxazine resin has good thermal stability, Tg ≥ 200°C, and low thermal expansion, which meets the requirements of mechanical properties and electrical properties of the copper clad laminate. The PPO resin has good dimensional stability, good heat resistance and water resistance, which is beneficial to improving the heat resistance and flame retardancy of the board. The biphenyl epoxy resin increases the thermosetting property while reducing the dielectric loss.

[0031] (3) The copper clad laminate provided by the present invention has a dielectric constant of <3.0, a dielectric loss (10G) <0.003, a Tg>210°C, a T288>120 minutes, a flame retardancy reaching FV-0 level, and a peel strength>0.9N / mm. DETAILED DESCRIPTION

[0032] The following specific embodiments illustrate the implementation of the present invention, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Although the description of the present invention will be introduced in conjunction with the preferred embodiment, this does not mean that the features of this invention are limited to this implementation. On the contrary, the purpose of introducing the invention in conjunction with the implementation is to cover other options or modifications that may extend based on the claims of the present invention. In order to provide a deep understanding of the present invention, the following description will include many specific details. The present invention can also be implemented without using these details. In addition, in order to avoid confusion or blurring the focus of the present invention, some specific details will be omitted in the description. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0033] Example 1

[0034] A method for preparing a high-frequency and high-speed copper-clad laminate comprises the following steps:

[0035] 1. Preparation of copper clad laminate glue:

[0036] S1: At room temperature, 54 parts of polyacenaphthylene resin, 12 parts of benzoxazine resin, 23 parts of PPO resin, 17 parts of biphenyl epoxy resin, 0.35 parts of DDS, 21 parts of toluene solvent and 18 parts of xylene solvent are added to a container and stirred to fully dissolve to obtain a solution;

[0037] S2: At room temperature, add 0.23 parts by weight of dimethyltetraethylimidazole to the solution of S1 and stir to fully dissolve it;

[0038] S3: By weight, 19 parts of aluminum hydroxide and 41 parts of silicon powder are added to the mixed solution of S2 and stirred evenly to fully emulsify to obtain an emulsion;

[0039] S4: In parts by weight, 13 parts of xylene solvent and 13 parts of toluene solvent were added to the emulsion in S3 to adjust the viscosity, and the mixture was stirred evenly. The gelling time of the glue was 253 s, and a uniform and stable copper clad laminate glue was obtained.

[0040] 2. Preparation of prepreg:

[0041] The adhesive solution obtained in S4 was evenly distributed on the Low DK glass fiber cloth, and the glass fiber cloth was baked in an oven at 185°C for 3 minutes to obtain a prepreg; the prepreg had a uniform appearance and a glue content of 56wt%.

[0042] 3. Preparation of copper clad laminate:

[0043] Four semi-cured sheets were stacked as required, and the upper and lower surfaces were covered with 18-micron copper foil. In a vacuum press with a pressure of 5 MPa and a temperature of 160°C, they were hot pressed for 3 hours and kept warm for 1 hour to obtain a high-frequency and high-speed copper-clad laminate.

[0044] Example 2

[0045] A method for preparing a high-frequency and high-speed copper-clad laminate comprises the following steps:

[0046] 1. Preparation of copper clad laminate glue:

[0047] S1: At room temperature, 60 parts of polyacenaphthylene resin, 18 parts of benzoxazine resin, 23 parts of PPO resin, 20 parts of biphenyl epoxy resin, 0.5 parts of DDS, 30 parts of toluene solvent and 23 parts of xylene solvent are added to a container and stirred to fully dissolve to obtain a solution;

[0048] S2: At room temperature, add 0.35 parts by weight of dimethyltetraethylimidazole to the solution of S1 and stir to fully dissolve it;

[0049] S3: Add 23 parts of aluminum hydroxide and 47 parts of silicon powder by weight to the mixed solution of S2 and stir evenly to fully emulsify to obtain an emulsion;

[0050] S4: By weight, 11 parts of xylene solvent and 11 parts of toluene solvent were added to the emulsion of S3 to adjust the viscosity, and the mixture was stirred evenly. The gelling time of the adhesive was 263s, and a uniform and stable adhesive for copper clad laminate was obtained.

[0051] 2. Preparation of prepreg:

[0052] The adhesive obtained in S4 is evenly distributed on the Low DK glass fiber cloth, and the glass fiber cloth is baked in an oven at 185°C for 2 minutes to obtain a prepreg; the prepreg has a uniform appearance and a glue content of 50wt%.

[0053] 3. Preparation of copper clad laminate:

[0054] Stack 4 semi-cured sheets as required, cover the upper and lower surfaces with 18-micron copper foil, and hot-press for 3 hours and keep warm for 1 hour in a vacuum press at a pressure of 12 MPa and a temperature of 180°C to obtain a high-frequency and high-speed copper-clad laminate.

[0055] Example 3

[0056] A method for preparing a high-frequency and high-speed copper-clad laminate comprises the following steps:

[0057] 1. Preparation of copper clad laminate glue:

[0058] S1: At room temperature, 70 parts of polyacenaphthylene resin, 20 parts of benzoxazine resin, 26 parts of PPO resin, 26 parts of biphenyl epoxy resin, 0.53 parts of DDS, 30 parts of toluene solvent and 22 parts of xylene solvent are added to a container and stirred to fully dissolve to obtain a solution;

[0059] S2: At room temperature, add 0.45 parts by weight of dimethyltetraethylimidazole to the solution of S1 and stir to fully dissolve it;

[0060] S3: Add 36 parts of aluminum hydroxide and 40 parts of silicon powder by weight to the mixed solution of S2 and stir evenly to fully emulsify to obtain an emulsion;

[0061] S4: In parts by weight, 12 parts of xylene solvent and 12 parts of toluene solvent were added to the emulsion of S3 to adjust the viscosity, and the mixture was stirred evenly. The gelling time of the glue was 267s, and a uniform and stable copper clad laminate glue was obtained.

[0062] 2. Preparation of prepreg:

[0063] The obtained adhesive solution was evenly distributed on the Low DK glass fiber cloth, and the glass fiber cloth was baked in an oven at 185° C. for 3.5 minutes to obtain a prepreg; the obtained prepreg had a uniform appearance and a glue content of 53 wt%.

[0064] 3. Preparation of copper clad laminate:

[0065] Four semi-cured sheets are stacked as required, and the upper and lower surfaces are covered with 18-micron copper foil. In a vacuum press with a pressure of 17 MPa and a temperature of 210°C, they are hot pressed for 3 hours and kept warm for 1 hour to obtain a high-frequency and high-speed copper-clad laminate.

[0066] Comparative Example 1

[0067] A method for preparing a copper clad laminate comprises the following steps:

[0068] 1. Preparation of copper clad laminate glue:

[0069] At room temperature, 60 parts by weight of cyanate resin, 11 parts by weight of bismaleimide resin, 20 parts by weight of polytetrafluoroethylene resin, 20 parts by weight of PPO resin, 0.2 parts by weight of dicyandiamide curing agent, 75 parts by weight of xylene solvent, 0.03 parts by weight of imidazole and 55 parts by weight of aluminum hydroxide filler are added into a container and stirred to fully dissolve the mixture to obtain a solution;

[0070] 2. Preparation of prepreg:

[0071] The above-obtained adhesive solution was completely and evenly impregnated with ordinary glass fiber cloth, and baked in an oven at 200°C for 5 minutes to obtain a semi-cured sheet with an adhesive content of 55wt%.

[0072] 3. Preparation of copper clad laminate:

[0073] Two prepregs were stacked as required, and the upper and lower surfaces were covered with 18-micron copper foil. They were hot-pressed for 1.5 hours in a vacuum press at a pressure of 5 MPa and a temperature of 150°C to obtain a high-frequency and high-speed copper-clad laminate.

[0074] Comparative Example 2

[0075] A method for preparing a copper clad laminate comprises the following steps:

[0076] 1. Preparation of copper clad laminate glue: at room temperature, add 50 parts of polyacenaphthylene resin, 15 parts of bismaleimide resin, 18 parts of tetrabromobisphenol A resin, 30 parts of cardanol modified phenolic resin, 0.1 parts of dicyandiamide curing agent, 70 parts of xylene solvent, 0.05 parts of imidazole and 50 parts of aluminum hydroxide filler into a container and stir to fully dissolve them to obtain a solution;

[0077] 2. Preparation of prepreg:

[0078] The obtained adhesive solution was evenly distributed on the Low DK glass fiber cloth, and the glass fiber cloth was baked in an oven at 185° C. for 3.5 minutes to obtain a prepreg; the obtained prepreg had a uniform appearance and a glue content of 53 wt%.

[0079] 3. Preparation of copper clad laminate:

[0080] Four semi-cured sheets are stacked as required, and the upper and lower surfaces are covered with 18-micron copper foil. In a vacuum press with a pressure of 17 MPa and a temperature of 210°C, they are hot pressed for 3 hours and kept warm for 1 hour to obtain a high-frequency and high-speed copper-clad laminate.

[0081] Comparative Example 3

[0082] A method for preparing a copper clad laminate comprises the following steps:

[0083] 1. Preparation of copper clad laminate adhesive: At room temperature, add 80 parts of polyacenaphthylene resin, 30 parts of furan resin, 25 parts of phosphorus-containing phenolic resin, 0.7 parts of dicyandiamide curing agent, 85 parts of xylene solvent, 0.10 parts of imidazole and 56 parts of aluminum hydroxide filler into a container and stir to fully dissolve them to obtain a solution;

[0084] 2. Preparation of prepreg:

[0085] The obtained adhesive solution was evenly distributed on the Low DK glass fiber cloth, and the glass fiber cloth was baked in an oven at 185° C. for 3.5 minutes to obtain a prepreg; the obtained prepreg had a uniform appearance and a glue content of 53 wt%.

[0086] 3. Preparation of copper clad laminate:

[0087] Four semi-cured sheets are stacked as required, and the upper and lower surfaces are covered with 18-micron copper foil. In a vacuum press with a pressure of 17 MPa and a temperature of 210°C, they are hot pressed for 3 hours and kept warm for 1 hour to obtain a high-frequency and high-speed copper-clad laminate.

[0088] Test method description:

[0089] (1) Dielectric constant: GB / T 4722-2017-8.5;

[0090] (2) Dielectric loss (10G): GB / T 4722-2017-8.5;

[0091] (3)Tg(DSC): GB / T 4722-2017-6.7.1;

[0092] (4)T288: GB / T 4722-2017-6.11;

[0093] (5) Peel strength (N / mm): GB / T 4722-2017-7.2.1;

[0094] (6) Flame retardancy: GB / T 4722-2017-6.4.1;

[0095] The test data of each embodiment and comparative example are shown in Table 1.

[0096] Table 1 Test data of each embodiment and comparative example

[0097]

[0098] By comparing the test experimental data in Table 1, it can be seen that the dielectric constant of the copper clad laminate of the embodiment is <3.0, the dielectric loss (10G) is <0.003, Tg>210°C, T288>120 minutes, the flame retardancy reaches FV-0 level, and the peel strength is >0.9N / mm.

[0099] Compared with comparative examples 1-3, the dielectric constant, dielectric loss, Tg and other indicators of examples 1-3 are significantly improved, and other basic indicators of examples 1-3 are also better than those of comparative examples 1-3. It can be seen that the copper clad laminate prepared by the copper clad laminate glue used in the present invention has a lower dielectric constant, low loss and high frequency compatibility, while other indicators are not reduced compared with the existing copper clad laminate.

[0100] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A copper clad laminate adhesive, characterized in that: The invention comprises resin, curing agent, catalyst, filler and solvent; the resin comprises polyacenaphthylene resin.

2. The copper clad laminate adhesive according to claim 1, characterized in that: The resin also includes benzoxazine resin, PPO resin, and biphenyl epoxy resin.

3. The copper clad laminate adhesive according to claim 2, characterized in that: The invention comprises the following components in parts by weight: 53-71 parts of polyacenaphthylene resin, 10-22 parts of benzoxazine resin, 22-26 parts of PPO resin, 14-28 parts of biphenyl epoxy resin, 0.3-0.6 parts of curing agent, 0.21-0.46 parts of catalyst, 59-77 parts of filler and 58-93 parts of solvent.

4. The copper clad laminate adhesive according to any one of claims 1 to 3, characterized in that: The curing agent is DDS, the catalyst is dimethyltetraethylimidazole, the filler is aluminum hydroxide and / or silicon powder, and the solvent is xylene and / or toluene.

5. A method for preparing a copper clad laminate adhesive as claimed in any one of claims 1 to 4, characterized in that: The steps include: S1: At room temperature, add resin, curing agent and part of solvent into a container and stir to dissolve to obtain a solution; S2: At room temperature, add the catalyst into the solution of S1 and stir to dissolve to obtain a mixed solution; S3: Add the filler into the mixed solution of S2 and stir evenly to obtain an emulsion; S4: adding the remaining part of the solvent into the emulsion of S3, stirring and gelling, and obtaining the copper clad laminate glue.

6. The method for preparing the copper clad laminate adhesive according to claim 5, characterized in that: In S4, the gelation time is 250 to 270 seconds.

7. The method for preparing the copper clad laminate adhesive according to claim 5, characterized in that: In S1, part of the solvent includes 20 to 40 parts of toluene and 18 to 27 parts of xylene, by weight; in S4, the remaining part of the solvent includes 10 to 13 parts of xylene and 10 to 13 parts of toluene, by weight.

8. A copper clad laminate, characterized in that: The copper clad laminate is prepared using the adhesive solution described in any one of claims 1 to 4.

9. A method for preparing a copper clad laminate as claimed in claim 8, characterized in that: The steps include: (1) The copper clad laminate adhesive is completely and evenly impregnated with the glass fiber cloth, and then baked in an oven at 150-200°C for 2-4 minutes to obtain a prepreg; (2) Take several prepregs with smooth surfaces and uniform coating, stack them, attach copper foil on the top and bottom, place them in a vacuum hot press with a pressure of 5-17 MPa and a temperature of 160-210°C, hot press for 2-4 hours and keep warm for 0.5-2 hours to obtain a copper clad laminate.

10. The method for preparing a copper clad laminate according to claim 9, characterized in that: The adhesive content of the prepreg is 49-57 wt %.

Citation Information

Patent Citations

  • Halogen-free resin composition and prepreg and laminate prepared therefrom

    CN104371273A

  • Preparation method of low-cost and low-loss copper clad plate for high-speed and high-frequency field

    CN110421928A

  • Preparation method of copper-clad plate with high Tg, low Dk and low Df

    CN115447235A

  • Resin composition for wiring board material, and prepreg, film with resin, metal foil with resin, metal foil-clad laminate, and wiring board using same

    CN115698183A

  • Resin composition, prepreg, film with resin, metal foil with resin, metal foil-clad laminate, and wiring board

    CN117120536A